Ketiadaan Standar Operasional Prosedur Teknis dalam Pengawasan Penahanan Ijazah: Kajian Yuridis atas Perlindungan Hak Pekerja - Varuqa Tur Rodia Arief (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the legal implications arising from the absence of appropriate technical instruments in supervising the practice of diploma withholding by companies, a matter that has long been mistakenly framed as a